La primera luna llena de gatita - Henkes, Kevin (Greenwillow Books, 2006)
When Kitten mistakes the full moon for a bowl of milk, she ends up tired, wet, and hungry trying to reach it. Translation of the 2005 Caldecott Medal winner.